Thermal Feature of a Modified Solar Phase Change Material Storage Wall System - Chenglong Luo; Lijie Xu; Jie Ji; Mengyin Liao; Dan Sun (International Journal of Photoenergy)
This work is to study a novel solar PCM storage wall technology, that is, a dual-channel and thermal-insulation-in-the-middle type solar PCM storage wall (MSPCMW) system. The system has the following four independent functions, passive solar heating, heat preservation, heat insulation, and passive cooling, and it can agilely cope with the requirements of climatization of buildings in different seasons throughout the year and is exactly suitable for building in regions characterized by hot summer and cold winter. The present work experimentally analyzes thermal feature of the system working in summer and winter modes, respectively.